Efforts to Protect Indonesian Waters as the World's Maritime Axis - Novia Mungawanah; Elen Anedya Frahma (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
Indonesia is known as one of the largest archipelagic countries in the world, consisting of 17,508 islands, with a sea area reaching 5.8 million km² and a coastline of 81,000 km. With prominent maritime characteristics and socio-cultural diversity, a special strategy is needed so that Indonesia can realize itself as a sovereign and resilient maritime nation. By restoring the nation's identity as a maritime nation, maximizing maritime potential for national economic equality, and safeguarding maritime interests and security, the global maritime axis concept seeks to establish Indonesia as a sizable, powerful, expansive, and prosperous maritime nation. This study uses a normative juridical approach method with data collection techniques through literature studies. The data reviewed are secondary data, such as scientific literature, journals, and expert opinions. The legal sources analyzed include primary legal materials, including laws, three Presidential Decrees, and relevant conventions. Additionally, tertiary data such as dictionaries and internet sources were utilized to support the analysis in this study. The role and responsibilities of the Indonesian Navy (TNI AL) are a crucial component in carrying out maritime diplomacy. The TNI AL not only cooperates with other countries to ensure the security and safety of shipping but also plays a role in strengthening Indonesia's recognition at the global level as the Global Maritime Axis. Maritime diplomacy is also carried out to support law enforcement and bolster the nation's sovereignty in maritime areas. The application of the five main pillars of maritime diplomacy launched during President Jokowi's administration has proven effective in handling and eradicating crime in national waters. Thus, efforts to safeguard Indonesia's maritime territory and realize Indonesia's vision as a global maritime axis can be achieved.